Latin america 1965-1975: the street as scenery of situations ascertaining a political art. study of two cases (2010)
At the end of the sixties and beginning of the seventies, transformations in the Latin American art occurred, narrowly related with the political and social situation in our countries. The present article focuses in two Argentinean cases through which the city value appears deeply recognized, and from there, the street as scenery for the performance of artistic interventions highly compromised with the social-political context in where they took place.